GTPase Activating Protein (Sh3 Domain) Binding Protein 1 Regulates the Processing of MicroRNA-1 during Cardiac Hypertrophy. - Minzhen He; Zhi Yang; Maha Abdellatif; Danish Sayed (PLoS ONE)
Background MicroRNAs (miR) are small, posttranscriptional regulators, expressed as part of a longer primary transcript, following which they undergo nuclear and cytoplasmic processing by Drosha and Dicer, respectively, to form the functional mature ~20mer that gets incorporated into the silencing complex. Others and we have shown that mature miR-1 levels decrease with pressure-induced cardiac hypertrophy, however, there is little or no change in the primary transcript encompassing miR-1 stem-loop, suggesting critical regulatory step in microRNA processing. The objective of this study was to investigate the underlying mechanisms regulating miR-1 expression in cardiomyocytes. Results Here we report that GTPase-activating protein (SH3 domain) binding protein 1 (G3bp1), an endoribonuclease regulates miR-1 processing in cardiomyocytes. G3bp1 is upregulated during cardiac hypertrophy and restricts miR-1 processing by binding to its consensus sequence in the pre-miR-1-2 stem-loop. In accordance, exogenous G3bp1 is sufficient to reduce miR-1 levels, along with derepression of miR-1 targets; General transcription factor IIB (Gtf2b), cyclin dependent factor 9 (Cdk9) and eukaryotic initiation factor 4E (Eif4e). While Cdk9 and Gtf2b are essential for transcription, Eif4e is required for translation. Thus, downregulation of miR-1 is necessary for increase in these molecules. Similar to miR-1 knockdown, G3bp1 overexpression is not sufficient for development of cardiac hypertrophy. Conversely, knockdown of G3bp1 in hypertrophying cardiomyocytes inhibited downregulation of miR-1 and upregulation of its targets along with restricted hypertrophy, suggesting that G3bp1 is necessary for development of cardiac hypertrophy. These results indicate that G3bp1-mediated inhibition of miR-1 processing with growth stimulation results in decrease in mature miR-1 and, thereby, an increase of its targets, which play fundamental roles in the development of hypertrophy. Conclusion G3bp1 posttranscriptionally regulates miRNA-1 processing in the heart, and G3bp1 mediated downregulation of mature miRNA-1 levels is required for the derepression of its targets and increase in gene expression during cardiac hypertrophy.